Estimating the Taylor Rule in the time-frequency domain - Conraria, Luís Aguiar (2014)
We assess U.S. monetary policy across time and frequencies in the framework of the Taylor Rule (TR). First, we portray the deviations between policy interest rates and the TR-prescribed rates with a set of continuous wavelet tools, comprising the coherency, phase-diference and gain. Then, using their multivariate counterparts, including a multivariate generalization of the wavelet gain, we estimate the TR coefficients in the time-frequency domain. We uncover a set of new stylized facts of the TR implicit in U.S. monetary policy that would not be possible to detect with pure time- or frequency-domain methods, nor with the time-frequency domain tools available thus far.